ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKSPEMBANGUNAN MANUSIA DI DKI JAKARTA PADA TAHUN 2016-2020 - Oktarizain Dida Pradana (2022)
The Human Development Index is an index used to determine the success of development in an area by using indicators of education, health, and welfare to make up the Index. This study aims to determine the effect of government spending on education, government spending on health, number of schools, number of hospitals, and number of poor people on the Human Development Index in 6 DKI Jakarta Admission Cities and Municipality. This study uses literature studies as its research method and quantitative data which is secondary data obtained from the publications of the Central Bureau of Statistics in the 2016-2020 period. Panel data regression method is the method used in this study which results in government spending on education, government spending on health, number of hospitals, having a significant effect while the number of schools and the number of poor people have no effect on the Human Development Index in DKI Jakarta.